2014
DOI: 10.1051/matecconf/20141407004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of abnormal grain coarsening in Alloy 718

Abstract: Abstract. Even though the phenomenon of abnormal grain coarsening (AGC) or "exploded grains" has been known to occur in Alloy 718 industrial forgings there is still no satisfactory explanation for it. For this reason, detailed microstructure analysis has been carried out in normal and abnormal regions. Electron Backscatter Diffraction (EBSD) was employed to determine grain size, boundary distribution and measure stored energy, while backscattered imagining in a FEGSEM was used to measure δ precipitate size and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The abnormal microstructures appear to contain a high proportion of annealing twin boundaries [1], similar to those found in strain annealed steels [2][3][4]. However there are some fundamental differences between the conditions under which these microstructures are formed.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…The abnormal microstructures appear to contain a high proportion of annealing twin boundaries [1], similar to those found in strain annealed steels [2][3][4]. However there are some fundamental differences between the conditions under which these microstructures are formed.…”
Section: Introductionmentioning
confidence: 55%
“…During a trial forging of an Alloy 718 component Otto Fuchs AG observed an abnormally coarse microstructure that was not predicted by current recrystallization models [1]. These abnormal grains appeared after the solution heat treatment (SHT).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The exact mechanisms underpinning the occurrence of AGG are still unclear and remain a subject of much interest and research. Though debate on specific mechanisms exists, most authors agree that the formation of AGG is related to low-energy, high-mobility grain boundaries such as ∑3 and its variants (e.g., ∑9 and ∑27) [8][9][10][11][12][13][14][15][16]. This is of note as Grain Boundary Engineering (GBE) is a specific type of thermomechanical process used to improve material properties by altering their grain boundary network and often resulting in increased frequency of ∑3 boundaries [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Gabb et al reported a similar reduction in fatigue life for a low solvus high refractory (LSHR) nickel-based superalloy when abnormally large grains were present within the microstructure [5]. While there still exists much debate regarding the specific mechanisms for the onset of AGG, most authors agree that the formation of abnormal grains is commonly related to the selective migration of low-energy or high mobility grain boundaries [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%